Mapping perioperative randomised controlled trials in Sub-Saharan Africa: a scoping review - Collier, Laila (Department of Anaesthesia and Perioperative Medicine, 2025)
Background: Surgical and anesthesia care is an integral component of universal healthcare coverage. In Sub-Saharan Africa (SSA), 93% of the population lacks access to essential surgical services. Post-surgery mortality in Africa is double the global average. The involvement of anesthesiologists is crucial for improved outcomes. Perioperative research can produce context-specific solutions to challenges faced in the perioperative period. SSA conducts fewer randomized controlled trials (RCTs) than high-income countries, limiting its contribution to global evidence. Objectives: Our primary objectives were to document the geographical distribution of included RCTs, describe their characteristics, and evaluate the reporting quality using the Consolidated Standards of Reporting Trials (CONSORT)-2010-checklist. Methods: We followed the PRISMA Scoping Reviews (PRISMAScR) Checklist. We searched MEDLINE, the Cochrane Library, and Scopus. We identified anesthesia-related RCTs within SSA published from 2000 to 2022. Two independent reviewers screened potential studies, and extracted data in duplicate, with disagreements resolved through consensus or a third reviewer. Quantitative analysis was done with STATA 16 and we compared RCT quality pre-CONSORT-2010 to post-CONSORT-2010, using Pearson's chi-squared test or Fisher's exact test (as applicable), considering p<0.05 as statistically significant. data were summarized narratively Results: Of 3319 records, 169 eligible RCTs were identified, randomizing 45376 participants, with a mean sample size of 98. Between the years 2000 and 2022, there was an exponential trend towards an increasing number of RCTs in SSA (y = 1,5619e0,1051x). The RCTs were from 16 countries in SSA. Most studies were single-country, single-center, led by authors from Nigeria (63/169, 37.3 %) and South Africa (41/169, 24.3%). Most interventions were conducted intraoperatively (n = 125/169, 74%). Pharmacotherapy interventions were most investigated (n = 64/169, 37.9%), followed by analgesic interventions (n = 42/169, 24.9%). The surgical discipline most investigated was obstetrics (n = 51/169, 30.2%). The reporting quality was generally poor, with most RCTs not adhering to CONSORT guidelines and failing to register on a trial registry. Conclusion: This scoping review provides a comprehensive overview of anesthesia-related RCTs in SSA, highlighting limitations such as small sample sizes, under-representation of high surgical burden disciplines, and poor reporting of study outcomes. The clinical trial capacity is limited to a few countries and institutions, and the methodological quality remains poor despite reporting guidelines. There is an opportunity to enhance context-appropriate RCTs in SSA by prioritizing high-quality research through collaborative efforts. Our findings serve as a resource for researchers, funders, and policymakers in anesthesia research in Africa to improve future RCT designs and reporting.